Examination of an equine wobble twelve years after surgical placement of a Bagby basket - Dukti, S. A.; Robertson, J. T.; Bertone, A. L.; Samii, V. F.; Rosol, T. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Case report describing histological and radiographic examination of a stainless steel basket packed with autogenous bone graft at C5-C6 ten years prior to evaluation. The horse was ataxic prior to surgery and post-operatively competed at his intended performance level despite a non-osseous union in the cranial endplate of C6.
Keywords: Bagby basket; wobbler; cervical vertebral stenotic myelopathy